Study on the effectiveness of percutaneous needle tendo Achilles tenotomy in congenital talipes equinovarus children - P Madhuchandra; G Sunilsanthosh; K P Raju (Wolters Kluwer Medknow Publications, 2023)
Introduction: Congenital talipes equinovarus (CTEV) is one of the most common deformities that affects the human foot and ankle, and Ponseti method of correction is universally accepted procedure. Most of the patients need a percutaneous tenotomy of tendo Achilles for residual equinus deformity. Various methods of tenotomy such as cataract knife, No. 11 blade, and 21-G needle are available. We studied the effectiveness of percutaneous needle tenotomy of the Achilles tendon in CTEV children for residual equinus deformity. Materials and Methods: Forty-three patients of serially manipulated and casted CTEV patients were subjected to a percutaneous needle tenotomy at our institute, followed by cast and orthosis. Tenotomy and regeneration were confirmed ultrasonologically and complete tenotomy was demonstrated by animal cadaver study. Results: All the patients were followed up regularly and an average of 25° of passive dorsiflexion was achieved at an average of 2-year follow-up. No cases of skin scarring, neurovascular compromise, stiffness, or cast complications were noted in our series. Conclusion: We conclude that percutaneous needle tenotomy for residual equinus deformity in a serially casted CTEV patient is a simple, effective, and safe method in giving a functionally and cosmetically good plantigrade foot.